A Distinctly Indian Body? K.V. Iyer and Physical Culture in 1930s India. Issue 12 (13th August 2019) - Ramachandran, Aishwarya; Heffernan, Conor
Abstract: Focusing on the career of K.V. Iyer, an Indian physical culturist of international renown, the following paper represents an in-depth discussion of exercise and bodybuilding practices in 1930s India. Through an exploration of Iyer's life, correspondence and exercise courses, it is argued that Iyer can be used as a prism through which ideas of colonial struggle, nationalism and modernity in India can be explored. Combining Western and Indian thought, Iyer sought to rally Indian men to begin exercising so as to cast aside ill behaviours and rejuvenate the Indian race. Deeply concerned with masculinity, Iyer's writings were infused with a nationalist ethos informed by scientific ideals. In discussing Iyer's previously uncovered physical culture enterprise, the paper begins with an overview of physical culture in 1930s India before Iyer's life and writings are examined. Following this the paper highlights Iyer's transnational approach, which saw the physical culturist write to others in England and the United States to great acclaim. In doing so, the paper addresses a dearth in the literature surrounding Iyer while contributing new understandings to Indian exercise practices in the mid-twentieth century.